Comparison of wiping and rinsing techniques after oral care procedures in critically ill patients during endotracheal intubation and after extubation: A prospective cross‐over trial. Issue 1 (26th June 2018) - Muramatsu, Keita; Matsuo, Koichiro; Kawai, Yusuke; Yamamoto, Tsukasa; Hara, Yoshitaka; Shimomura, Yasuyo; Yamashita, Chizuru; Nishida, Osamu
Abstract: Aim: Endotracheal intubation of critically ill patients increases the risk of aspiration pneumonia, which can be reduced by regular oral care. However, the rinsing of the residual oral contaminants after mechanical cleaning carries the risk of aspirating the residue during the intubation period. Removing the contaminants by wiping with mouth wipes could be an alternative to rinsing with water because of no additional fluid. This study tested: (i) the amount of oral bacteria during endotracheal intubation and after extubation; and (ii) the changes in the bacterial count during oral care procedures. Methods: Thirty‐five mechanically ventilated patients in the intensive care unit were enrolled. The amount of bacteria on the dorsal tongue surface was counted before and following oral care and then after the elimination of contaminants either by rinsing with water and suctioning or by wiping with mouth wipes. The oral bacterial amount was compared statistically between the intubation and extubation status and among set time points during the oral care procedure. Results: The oral bacterial count was significantly decreased after extubation. During the oral care procedure, the oral bacterial amount was significantly lower after eliminating the contaminants either by rinsing or wiping, with no remarkable difference between the elimination techniques. Conclusions: The findings suggest that the oral bacterial amount is elevated during endotracheal intubation, which could increase the risk of aspiration pneumonia. The significant reduction in the bacterial count by wiping indicates that it might be a suitable alternative to rinsing for mechanically ventilated patients.